Fungal Symbionts Enhance N-Uptake for Antarctic Plants Even in Non-N Limited Soils - Acuña-Rodríguez, Ian S.; Galán, Alexander; Torres-Díaz, Cristian; Atala, Cristian; Molina-Montenegro, Marco A. (Frontiers in Microbiology, 2020)
Plant-fungi interactions have been identified as fundamental drivers of the plant host performance, particularly in cold environments where organic matter degradation rates are slow. Nevertheless, these positive effects of fungal endophytes appear to be modulated by the composition and amount of the N pool in the soil, being greater when plant hosts are growing where N is scarce as is the case of Antarctic soils. Nevertheless, in some coastal areas of this continent, seabirds and marine mammal colonies exert, through their accumulated faeces and urine a strong influence on the edaphic N content surrounding their aggregation points. To evaluate if the fungal symbionts (root endophytes), associated to the only two Antarctic vascular plants Colobanthus quitensis and Deschampsia antarctica, act as N-uptake enhancers, even in such N-rich conditions as those found around animal influence, we assessed, under controlled conditions, the process of N mineralization in soil by the accumulation of NH4+ in the rizhosphere and the biomass accumulation of plants with (E+) and without (E-) fungal symbionts. Complementarily, taking advantage of the isotopic N-fractionation that root-fungal symbionts exert on organic N molecules during its acquisition process, we also determined if endophytes actively participate in the Antarctic plants N-uptake, when inorganic N is not a limiting factor, by estimating the 15N isotopic signatures in leaves. Overall, symbiotic interaction increased the availability of NH4+ in the rhizosphere of both species. As expected, the enhanced availability of inorganic N resulted in a higher final biomass in E+ compared with E- plants of both species. In addition, we found that the positive role of fungal symbionts was also actively linked to the process of N-uptake in both species, evidenced by the contrasting 15N signatures present in E+ (-0.4 to -2.3 ‰) relative to E- plants (2.7 to 3.1 ‰). In conclusion, despite being grown under rich N soils, the two Antarctic vascular plants showed that the presence of root-fungal endophytes, furthermore enhanced the availability of inorganic N sources in the rhizosphere, has a positive impacts in their biomass, remarking the active participation of these endophytes in the N-uptake process for plants inhabiting the Antarctic continent.